Aktivitas Larvasida Aedes aegypti Ekstrak Kayu Jati Hasil Ekstraksi Hidrotropi (Larvicidal Activity Against Aedes aegypti of Teak Wood Extracts from Hydrotropic Extraction) - Rita K Sari; Idris N Iskandar; S Priambodo; Regita Pramesti; Livia T Amalia (Jurnal Ilmu dan Teknologi Kayu Tropis, 2017)
This study aimed to determine the yield and chemical content of teak extracts from hydrotropic extraction and larvalidal activity test against Aedes aegypti. The teak wood powder was extracted with urea (U) and natirum acetate (NA) solutions at 1M and 2M with physical treatment of magnetic stirrer (MS) and microwave (MS). The composition of chemical compound of extracts were determined by GC-MS. The larvicidal activity test were conducted on insted larvae of A. aegypti mosquito III. The results showed that the yield of NA extracts were higher (1.08-2.31%) than U extracts (0.72-1.68%). The increased of solvent concentration increased the extract yield. The physical treatment of MS produced a higher extract than MW. The NA extracts were dominated by acetic acid (16.53-40.21%), whereas the U extracts contained various dominant compounds. Both NA and U extracts contained tectoqinon, eugenol, farnesol, o-methoxyl benzene alcohol, methoxydeugenol, 3-penten-2-one, and tetracosahexaene with different levels. The U extracts were detected containing tectoqinon (0.66-1.79%), while the Na extract which was extracted with 1M NA and got MW treatment was detected contain tectoqinon (0.42%). The NA extracts were classified as active as larvacidal to A. aegypti, while U extracts were classified as inactive as larvacidal to A. aegypti.Keywords: Aedes aegypti, hydrotropic extraction, larvacidal, teak wood extract